Cyclodextrins and Iatrogenic Hearing Loss: New Drugs with Significant Risk - Crumling, Mark A.; King, Kelly A.; Duncan, R. Keith (Frontiers in Cellular Neuroscience, 2017)
Cyclodextrins are a family of cyclic oligosaccharides with widespread usage in medicine, industry, and basic sciences owing to their ability to solubilize and stabilize guest compounds. In medicine, cyclodextrins primarily act as a complexing vehicle and consequently serve as powerful drug delivery agents. Recently, uncomplexed cyclodextrins have emerged as potent therapeutic compounds in their own right, based on their ability to sequester and mobilize cellular lipids. In particular, 2-hydroxypropyl-β-cyclodextrin (HPβCD) has garnered attention because of its cholesterol chelating properties, which appear to treat a rare neurodegenerative disorder and to promote atherosclerosis regression related to stroke and heart disease. Despite the potential health benefits, use of HPβCD has been linked to significant hearing loss in several species, including humans. Evidence in mice supports a rapid onset of hearing loss that is dose-dependent. Ototoxicity can occur following central or peripheral drug delivery, with either route resulting in the preferential loss of cochlear outer hair cells (OHCs) within hours of dosing. Inner hair cells and spiral ganglion cells are spared at doses that cause ~85% OHC loss; additionally, no other major organ systems appear adversely affected. Evidence from a first-to-human phase 1 clinical trial mirrors animal studies to a large extent, indicating rapid onset and involvement of OHCs. All patients in the trial experienced some permanent hearing loss, although a temporary loss of function can be observed acutely following drug delivery. The long-term impact of HPβCD use as a maintenance drug, and the mechanism(s) of ototoxicity, are unknown. β-cyclodextrins preferentially target membrane cholesterol, but other lipid species and proteins may be directly or indirectly involved. Moreover, as cholesterol is ubiquitous in cell membranes, it remains unclear why OHCs are preferentially susceptible to HPβCD. It is possible that HPβCD acts upon several targets—for example, ion channels, tight junctions, membrane integrity, and bioenergetics—that collectively increase the sensitivity of OHCs over other cell types.